Probabilistic Foundations of Rabbinic Methods for Resolving Uncertainty - Koppel Moshe (Studia Humana, 2017)
We consider several fundamental principles of rabbinic approaches to handling uncertainty for legal purposes. We find that non-numerical versions of ideas subsequently developed in the literature on interpretations of probabilistic statements are useful for explicating these rabbinic principles.